The Mid-Infrared Instrument for the James Webb Space Telescope, IV: The Low-Resolution Spectrometer. (4th January 2016) - Kendrew, Sarah; Scheithauer, Silvia; Bouchet, Patrice; Amiaux, Jerome; Azzollini, Ruymán; Bouwman, Jeroen; Chen, C. H.; Dubreuil, D.; Fischer, Sebastian; Glasse, Alistair; Greene, T. P.; Lagage, P.-O.; et al.
Abstract: The low-resolution spectrometer of the MIRI, which forms part of the imager module, will provide R ∼ 100 long-slit and slitless spectroscopy from 5 to 12 μm. The design is optimized for observations of compact sources, such as exoplanet host stars. We provide here an overview of the design of the LRS, and its performance as measured during extensive test campaigns, examining in particular the delivered image quality, dispersion, and resolving power, as well as spectrophotometric performance, flatfield accuracy, and the effects of fringing. We describe the operational concept of the slitless mode, which is optimally suited to transit spectroscopy of exoplanet atmospheres. The LRS mode of the MIRI was found to perform consistently with its requirements and goals.